Does Evidence Support the Use of Neural Tissue Management to Reduce Pain and Disability in Nerve-related Chronic Musculoskeletal Pain?: A Systematic Review With Meta-Analysis. Issue 11 (November 2016) - Su, Yunfeng; Lim, Edwin Choon Wyn
Abstract : Objectives: In nerve-related chronic musculoskeletal (MS) disorders, neural tissue management is used to relieve pain by balancing the relative movement of neural tissues and their surrounding tissues. To date, there has not been any review evaluating the magnitude of this treatment effect in nerve-related chronic MS pain. The aim of this review was to compare pain and disability in individuals with nerve-related chronic MS pain who were treated with neural tissue management with those who received minimal or other treatment approaches. Methods: Searches of 8 major electronic databases were conducted, and data on pain and disability scores were extracted. Meta-analyses (where possible) with either a fixed-effect(s) or random-effect(s) model, standardized mean differences (SMDs), and tests of heterogeneity were performed. Results: Twenty clinically controlled trials were identified and included in the meta-analyses. When compared with minimal intervention, neural mobilization provided superior pain relief (pooled SMD=−0.77; 95% confidence interval [CI], −1.11 to −0.42; P <0.0001), and reduction in disability (pooled SMD=−1.06; 95% CI, −1.97 to −0.14; P =0.02), after post hoc sensitivity analyses. No significant differences were found when comparing neural mobilization with other treatment approaches for pain (pooled SMD=−0.67; 95% CI, −2.03 to 0.69; P =0.33), after post hoc sensitivity analysis, and disability (pooled SMD=−0.03; 95% CI, −0.54 to 0.59; P =0.93). Discussion: Neural tissue management is superior to minimal intervention for pain relief and reduction of disability in nerve-related chronic MS pain. Existing evidence does not establish superiority of neural mobilization over other forms of intervention in reducing pain and disability in individuals with nerve-related chronic MS pain.